Non-alcoholic Fatty Liver Disease: Diagnosis and Treatment - Dewa Ayu Vania Novista Anjani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
NAFLD is a highly prevalent liver disease that encompasses various clinical presentations. Initially, patients are at high risk of experiencing cardiovascular events, while some may progress to advanced fibrosis or even cirrhosis, thus increasing the risk of liver decompensation and mortality. Accurate methods of diagnosing and managing NAFLD are crucial in order to minimize the impact of the disease. Moreover, the diagnosis of NAFLD is often overlooked by doctors and only receives attention when it leads to serious complications. The purpose of this literature review is to enhance the understanding of Non-alcoholic fatty liver disease, with a focus on discussing the methods of diagnosing and managing NAFLD based on published literature references from various databases. NAFLD can be diagnosed through a comprehensive approach involving clinical laboratory findings, radiological modalities, and biopsy. The management of NAFLD includes lifestyle modifications, pharmacological interventions, and liver transplantation. Despite the availability of various diagnostic methods for NAFLD in this era, biopsy remains the gold standard. The pharmacological treatment options for NAFLD are still limited, and the cornerstone of any treatment is diet, weight loss, and physical exercise. Early diagnosis and a comprehensive management approach can be beneficial for patients with NAFLD.